High Improvement in Conversion Efficiency of μc-SiGe Thin-Film Solar Cells with Field-Enhancement Layers - Shu-Hung Yu; Wei Lin; Yu-Hung Chen; Chun-Yen Chang (International Journal of Photoenergy)
The improved performance for hydrogenated microcrystalline silicon-germanium (μc-Si1−xGex:H, x~0.1) p-i-n single solar cells with hydrogenated microcrystalline silicon (μc-Si:H) field-enhancement layers (FELs) is demonstrated for the first time. The fill factor (FF) and conversion efficiency (η) increase by about 19% and 28% when the thickness of the μc-Si FEL is increased from 0 to 200 nm, it is attributed to the longer hole life-time and enhanced electric field in the μc-Si0.9Ge0.1:H layer. Therefore, we can successfully manufacture high-performance μc-SiGe:H solar cells with the thickness of absorbers smaller than 1 μm by conducting FELs. Moreover, the simulation tool is used to simulate the current-voltage (J-V) curve, thus we can investigate the carrier transport in the absorber of μc-Si0.9Ge0.1:H solar cells with different EFLs.